Heisenberg's quantum mechanics - Razavy, Mohsen (Singapore ; Hackensack, N.J. : World Scientific, 2011)
This book provides a detailed account of quantum theory with a much greater emphasis on the Heisenberg equations of motion and the matrix method.
The book features a deeper treatment of the fundamental concepts such as the rules of constructing quantum mechanical operators and the classical-quantal correspondence; the exact and approximate methods based on the Heisenberg equations; the determinantal approach to the scattering theory and the LSZ reduction formalism where the latter method is used to obtain the transition matrix. The uncertainty relations for a number of different observables are derived and discussed. A comprehensive chapter on the quantization of systems with nonlocalized interaction is included. Exact solvable models, and approximate techniques for solution of realistic many-body problems are also considered. The book takes a unified look in the final chapter, examining the question of measurement in quantum theory, with an introduction to the Bell's inequalities. --Book Jacket.
17.10. Scattering of Two Quasi-Particles -- 17.11. Bogoliubov Transformation for Fermions Interacting through Pairing Forces -- 17.12. Damped Harmonic Oscillator -- 18.1. Coherent State of the Radiation Field -- 18.2. Casimir Force -- 18.3. Casimir Force Between Parallel Conductors -- 18.4. Casimir Force in a Cavity with Conducting Walls -- 19.1. Theory of Natural Line Width -- 19.2. The Lamb Shift -- 19.3. Heisenberg's Equations for Interaction of an Atom with Radiation -- 20.1. EPR Experiment with Particles -- 20.2. Classical and Quantum Mechanical Operational Concepts of Measurement -- 20.3. Collapse of the Wave Function -- 20.4. Quantum versus Classical Correlations.
Includes bibliographical references and index.
Print version record.
English.
Keywords: Quantum theory; SCIENCE -- Physics -- Quantum Theory; Quantum theory; Physics; Physical Sciences & Mathematics; Atomic Physics; Electronic book; Electronic books